2006
DOI: 10.1080/01425690600556461
|View full text |Cite
|
Sign up to set email alerts
|

Reflexivity, learning identities and adult basic skills in the United Kingdom

Abstract: This paper reports on the findings of a small qualitative research project that examined the experiences of a group of adult learners attending a basic skills programme in the English Midlands during the late 1990s. It explores patterns of participation on such programmes and illustrates that early life course experiences can shape changing dispositions towards learning and forms of (dis)engagement from formal provision. The concept of reflexivity is used to help describe the differing contributions that struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
0
22
0
3
Order By: Relevance
“…She also notes that other modes may be identified. One of us has demonstrated elsewhere how distinctive forms of actor's reflexive self-talk are used to give meaning to, and in the process activate, the constraints and enablements of the social contexts in which they find themselves with regard to learning identities and participation in formal literacy classes (Cieslik, 2005).…”
Section: Transitions and Reflexivitymentioning
confidence: 99%
“…She also notes that other modes may be identified. One of us has demonstrated elsewhere how distinctive forms of actor's reflexive self-talk are used to give meaning to, and in the process activate, the constraints and enablements of the social contexts in which they find themselves with regard to learning identities and participation in formal literacy classes (Cieslik, 2005).…”
Section: Transitions and Reflexivitymentioning
confidence: 99%
“…These findings show that by participating in more engaging and positive experiences of learning within caring social environments the learners had begun to narrate a different sense of identity that had evolved in the face of events and reflections on those events (Cieslik, 2006). Within the programmes most of the learners had been recognized as competent, learnt how to engage with others, shared the resources commonly used to communicate and gone about their activities in ways that had given them 'an increasing sense of identity as a master practitioner' (Lave & Wenger, 1991, p. 111).…”
Section: Discussionmentioning
confidence: 99%
“…This power dimension is particularly foregrounded when working with people whose previous experiences have told them that they cannot easily learn new things. These experiences have been mainly derived from poor experiences of compulsory schooling and/or unhappy childhoods that, as many studies have found (see Barton et al, 2007;Cieslik, 2006;Tett, 2014;Worthman, 2008), have left them with not only low literacy skills but also low self-confidence.…”
Section: Partnerships Power and Learningmentioning
confidence: 99%